Marine Glycoconjugates: Trends and Perspectives - Stonik, Valentin A. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The books described marine glycoconjugates. Two articles concern microalgal metabolites such as steroid and sphingoid glycoconjugates, and a glycoprotein from a sea cucumber with interesting biological activities, respectively. One article discusses the fatty acid composition and thermotropic behavior of glycolipids and other membrane lipids of green macrophyte Ulva lactuca. Three articles cover lectin subjects. One review article analyzes perspectives of marine and freshwater lectins' application in experimental oncology and the therapy of oncological diseases; another article describes the use of a sponge lectin in the construction of a recombinant virus. The third article concerns the function of the immunity of a lectin in producing this compound crinoid. Two articles concern steroid glycosides from star?sh, and two others concern triterpene glycosides from sea cucumbers. One article describes the e?ect of a glycosaminoglycan from the sea cucumber Apostichopus japonicus on hyperglycemia in the liver of insulin-resistant mice. One article concerns the isolation of 10 new triterpene glycosides from a fungus associated with a sea cucumber. The article by Dworaczek et al. characterizes the O-speci?c polysaccharide (O-antigen) of a bacterial pathogen of common carp by chemical and immunochemical methods. In total, the Special Issue comprises14 articles, including the editorial and two reviews.